PENGARUH PEMBERIAN AUKSIN PADA STEK BATANG BUNI (Antidesma bunius) - Anggraini, Novita; Anna, Nelly (Universitas Cokroaminoto Palopo, 2024)
Buni (Antidesma bunius L. Spreng) was a potential plant species of the family Euphorbiaceae. The existence buni increasingly less, So it requireds effort for the multiplication of buni, one through by cuttings. Plant Growth Regulator (PGR) role in rooting cuttings was auxin. Naphtalene acetid acid (NAA) was pure synthesis auxin, whereas Rootone F was a type of commercial hormone consisting of several auxins. The research was to examine the effect of plant growth regulator NAA and Rootone F to growth cuttings of berry (Antidesma bunius L. Spreng). The design used was non factorial completely randomized design with 9 treatments and 4 replications. The results showed that using NAA (0.5 ppm, 1 ppm, 1.5 ppm, 2 ppm) and Rootone F (25 ppm, 50 ppm, 75 ppm, 100 ppm) have not been able to trigger the formation of roots at the cuttings buni. Shoot formation allegedly came from the food reserves on stem and environmental factors (temperature).